Rationality in The Pattern of Appointment and Dismissal Of Village Equipment Post Village Head Election in Pesawaran District Lampung Province - Marzuki Marzuki; Mansyur Achmad; Karno Karno (INVEST : Jurnal Inovasi Bisnis dan Akuntansi, 2023)
The background of this research is the dismissal and appointment of Village Apparatuses after the election of the village head in Pesawaran District. The dismissal and Appointment of village apparatuses that occurred in Pesawawan District included those who followed the rules and some who were not based on the rules. The "smooth" elite circulation managed by the elected Village Head is of course very interesting to analyze and become an academic discussion which according to the author feels it is also important to be photographed and discussed dialectically, if one sees the potential that should have occurred in the context of dismissal of village officials. Rationality of Decisions/Judgments with a Decision-Making Theory approach (Dietrich, 2010) The pattern of formal and material dismissal and appointment of village officials is in accordance with the provisions of laws and regulations as mandated in Law No. 6 of 2014, PP No. 43 of 2014, Permendagri No. 85 of 2015 and the District Regulation. Offer No. 8 of 2016, From the analysis of existing data, the following research conclusions were obtained: Efforts made by the Village Head in appointing and dismissing village officials: From the alternative decisions taken by the Head of Margorejo Village and the Head of Gayau Village, with the Social Action approach as a tool measuring the rationality of actions, the results obtained are: a) Margorejo Village has 3 (three) rational actions and 1 (one) irrational action in making decisions on the appointment and dismissal of village officials in its territory; b) Gayau Village has 4 (four) rational actions in making decisions on the appointment and dismissal of village officials in its territory. It can be said that the decision making for the appointment and dismissal of village officials carried out by the Head of Margorejo Village and Gayau Village was a rational action.